Drawing and emerging research: The acquisition of experiential knowledge through drawing as a methodological strategy. (July 2014) - Roberts, Amanda; Riley, Howard
The paper proposes the activity of drawing as a methodological strategy within a university research context. It is illustrated with examples from one of the authors' (Roberts) practice-based PhD research. The paper argues that drawing as a research method can be validated in a manner akin to the more established research methods associated with the range of research paradigms outlined in Denzin and Lincoln's Handbook of Qualitative Research . It is proposed that visual research methods are unique in their ability to produce experiential knowledge that can be shared through visual media but not easily articulated through language. The paper then argues that drawing's contribution as a visual research strategy has a more holistic and far-reaching potential within the university than other qualitative and quantitative research methods. In addition, visual research outputs operate as components of findings and conclusive evidence in the form of experiential knowledge that can enrich and extend language-based cognitive knowledge.